DDQ in mechanochemical C–N coupling reactions - Bera, Shyamal Kanti; Bhanja, Rosalin; Mal, Prasenjit (Beilstein Journal of Organic Chemistry, 2022)
2,3-Dichloro-5,6-dicyano-1,4-benzoquinone (DDQ) is a commonly known oxidant. Herein, we report that DDQ can be used to synthesize 1,2-disubstituted benzimidazoles and quinazolin-4(3H)-ones via the intra- and intermolecular C–N coupling reaction under solvent-free mechanochemical (ball milling) conditions. In the presence of DDQ, the intramolecular C(sp2)–H amidation of N-(2-(arylideneamino)phenyl)-p-toluenesulfonamides leads to 1,2-disubstituted benzimidazoles and the one-pot coupling of 2-aminobenzamides with aryl/alkyl aldehydes resulted in substituted quinazolin-4(3H)-one derivatives in high yields.
Keywords: ball mill; 1H-benzo[d]imidazole; C(sp2)–H amidation; DDQ; mechanochemistry; quinazolin-4(3H)-one

(untitled) - Hernández, J. G.; Bolm, C. (J. Org. Chem., 2017)

(untitled) - Ardila‐Fierro, K. J.; Hernández, J. G. (ChemSusChem, 2021)

(untitled) - Egorov, I. N.; Santra, S.; Kopchuk, D. S.; Kovalev, I. S.; Zyryanov, G. V.; Majee, A.; Ranu, B. C.; Rusinov, V. L.; Chupakhin, O. N. (Green Chem., 2020)

(untitled) - Tan, D.; Friščić, T. (Eur. J. Org. Chem., 2018)

(untitled) - Wang, G.-W. (Chem. Soc. Rev., 2013)

(untitled) - Mateti, S.; Mathesh, M.; Liu, Z.; Tao, T.; Ramireddy, T.; Glushenkov, A. M.; Yang, W.; Chen, Y. I. (Chem. Commun., 2021)

(untitled) - Gomollón-Bel, F. (Chem. Int., 2019)

(untitled) - Bose, A.; Mal, P. (Beilstein J. Org. Chem., 2019)

(untitled) - Achar, T. K.; Bose, A.; Mal, P. (Beilstein J. Org. Chem., 2017)

(untitled) - O’Neill, R. T.; Boulatov, R. (Nat. Rev. Chem., 2021)

(untitled) - Lou, S.-J.; Mao, Y.-J.; Xu, D.-Q.; He, J.-Q.; Chen, Q.; Xu, Z.-Y. (ACS Catal., 2016)

(untitled) - Das, D.; Bhosle, A. A.; Panjikar, P. C.; Chatterjee, A.; Banerjee, M. (ACS Sustainable Chem. Eng., 2020)

(untitled) - Bera, S. K.; Mal, P. (J. Org. Chem., 2021)

(untitled) - Alsharif, M. A.; Raja, Q. A.; Majeed, N. A.; Jassas, R. S.; Alsimaree, A. A.; Sadiq, A.; Naeem, N.; Mughal, E. U.; Alsantali, R. I.; Moussa, Z.; Ahmed, S. A. (RSC Adv., 2021)

(untitled) - Wendlandt, A. E.; Stahl, S. S. (Angew. Chem., Int. Ed., 2015)

(untitled) - Cheng, D.; Wu, L.; Deng, Z.; Xu, X.; Yan, J. (Adv. Synth. Catal., 2017)

(untitled) - Chen, Q.; Wen, C.; Wang, X.; Yu, G.; Ou, Y.; Huo, Y.; Zhang, K. (Adv. Synth. Catal., 2018)

(untitled) - Li, J.-S.; Xue, Y.; Fu, D.-M.; Li, D.-L.; Li, Z.-W.; Liu, W.-D.; Pang, H.-L.; Zhang, Y.-F.; Cao, Z.; Zhang, L. (RSC Adv., 2014)

(untitled) - Yi, H.; Liu, Q.; Liu, J.; Zeng, Z.; Yang, Y.; Lei, A. (ChemSusChem, 2012)

(untitled) - Pan, D.; Pan, Z.; Hu, Z.; Li, M.; Hu, X.; Jin, L.; Sun, N.; Hu, B.; Shen, Z. (Eur. J. Org. Chem., 2019)

(untitled) - Li, C.; Li, J.; Tan, C.; Wu, W.; Jiang, H. (Org. Chem. Front., 2018)

(untitled) - Yan, B.; Fu, Y.; Zhu, H.; Chen, Z. (J. Org. Chem., 2019)

(untitled) - Zhai, L.; Shukla, R.; Rathore, R. (Org. Lett., 2009)

(untitled) - Natarajan, P.; König, B. (Eur. J. Org. Chem., 2021)

(untitled) - Song, C.; Dong, X.; Yi, H.; Chiang, C.-W.; Lei, A. (ACS Catal., 2018)

(untitled) - Shen, Z.; Dai, J.; Xiong, J.; He, X.; Mo, W.; Hu, B.; Sun, N.; Hu, X. (Adv. Synth. Catal., 2011)

(untitled) - Mandal, T.; Azim, A.; Das, S.; De Sarkar, S. (Asian J. Org. Chem., 2022)

(untitled) - Sun, C.; Zheng, L.; Xu, W.; Dushkin, A. V.; Su, W. (Green Chem., 2020)

(untitled) - Hernández, J. G.; Turberg, M.; Schiffers, I.; Bolm, C. (Chem. – Eur. J., 2016)

(untitled) - Li, C.-J. (Chem, 2016)

(untitled) - Hermann, G. N.; Bolm, C. (ACS Catal., 2017)

(untitled) - Bariwal, J.; Van der Eycken, E. (Chem. Soc. Rev., 2013)

(untitled) - Hartwig, J. F. (Acc. Chem. Res., 2008)

(untitled) - Majumdar, B.; Sarma, D.; Bhattacharya, T.; Sarma, T. K. (ACS Sustainable Chem. Eng., 2017)

(untitled) - Ruiz-Castillo, P.; Buchwald, S. L. (Chem. Rev., 2016)

(untitled) - Sun, C.-L.; Shi, Z.-J. (Chem. Rev., 2014)

(untitled) - Louillat, M.-L.; Patureau, F. W. (Chem. Soc. Rev., 2014)

(untitled) - Carvalho, L. C. R.; Fernandes, E.; Marques, M. M. B. (Chem. – Eur. J., 2011)

(untitled) - Maiti, S.; Mal, P. (Adv. Synth. Catal., 2015)

(untitled) - Alam, M. T.; Maiti, S.; Mal, P. (Beilstein J. Org. Chem., 2018)

(untitled) - Li, Y.-F.; Wang, G.-F.; He, P.-L.; Huang, W.-G.; Zhu, F.-H.; Gao, H.-Y.; Tang, W.; Luo, Y.; Feng, C.-L.; Shi, L.-P.; Ren, Y.-D.; Lu, W.; et al. (J. Med. Chem., 2006)

(untitled) - Valdez, J.; Cedillo, R.; Hernández-Campos, A.; Yépez, L.; Hernández-Luis, F.; Navarrete-Vázquez, G.; Tapia, A.; Cortés, R.; Hernández, M.; Castillo, R. (Bioorg. Med. Chem. Lett., 2002)

(untitled) - Sondhi, S. M.; Rajvanshi, S.; Johar, M.; Bharti, N.; Azam, A.; Singh, A. K. (Eur. J. Med. Chem., 2002)

(untitled) - Sharpe, M.; Jarvis, B.; Goa, K. L. (Drugs, 2001)

(untitled) - Parua, S.; Das, S.; Sikari, R.; Sinha, S.; Paul, N. D. (J. Org. Chem., 2017)

(untitled) - Sahoo, S.; Pal, S. (J. Org. Chem., 2021)

(untitled) - Kung, P.-P.; Casper, M. D.; Cook, K. L.; Wilson-Lingardo, L.; Risen, L. M.; Vickers, T. A.; Ranken, R.; Blyn, L. B.; Wyatt, J. R.; Cook, P. D.; Ecker, D. J. (J. Med. Chem., 1999)

(untitled) - Chen, M.; Li, P.; Hu, D.; Zeng, S.; Li, T.; Jin, L.; Xue, W.; Song, B. (Bioorg. Med. Chem. Lett., 2016)

(untitled) - Chandrika, P. M.; Yakaiah, T.; Rao, A. R. R.; Narsaiah, B.; Reddy, N. C.; Sridhar, V.; Rao, J. V. (Eur. J. Med. Chem., 2008)

(untitled) - Cao, S.-L.; Feng, Y.-P.; Jiang, Y.-Y.; Liu, S.-Y.; Ding, G.-Y.; Li, R.-T. (Bioorg. Med. Chem. Lett., 2005)

(untitled) - Kikuchi, H.; Yamamoto, K.; Horoiwa, S.; Hirai, S.; Kasahara, R.; Hariguchi, N.; Matsumoto, M.; Oshima, Y. (J. Med. Chem., 2006)

(untitled) - Ozaki, K.-i.; Yamada, Y.; Oine, T.; Ishizuka, T.; Iwasawa, Y. (J. Med. Chem., 1985)

(untitled) - Batra, A.; Singh, K. N. (Eur. J. Org. Chem., 2020)

(untitled) - Cheng, D.; Bao, W. (J. Org. Chem., 2008)

(untitled) - Guo, X.; Zipse, H.; Mayr, H. (J. Am. Chem. Soc., 2014)